Zwisima na zwipise ndi fhethu ha zwifho: traditional hydrological knowledge, conservation and protection of groundwater among the Venda, northern South Africa - Magoma, Munyadziwa; Pikirayi, Innocent (Frontiers in Human Dynamics, 2025)
Springs are vital freshwater and hydrothermal groundwater sources. We pose the research question how springs are perceived in indigenous worldview and employ ethnographic and historical sources highlighting springs as sacred sites protected by myths and legends. The Venda regard water as a cultural entity deeply imbued with spiritual importance. Such knowledge is critical in conservation of groundwater, which surfaces through springs. Springs are not only associated with riverine headwaters, but also conform to particular drainage patterns, contributing to the overall water flow and drainage. This is of profound cultural importance where watershed and springs are associated with beginnings of life. Venda myths and legends demonstrate how such sacred environments regulated exploitation and conservation of biodiversity. Given modern infrastructure development, groundwater conservation must be located within particular indigenous worldviews.